Current insights suggest gabapentin-induced neurodegeneration - Priyanka Gupta; Rupal Shukla; Poornima Yadav; Tahniyat Ansari; Subha Shrivastava; Ratnesh Kumar Soni; Sudhi Shrivastava (International Journal of Basic & Clinical Pharmacology, 2026)
Antiepileptic drugs (AEDs) are commonly prescribed to treat epilepsy and other neurodegenerative disorders (NDs). Gabapentin (GBP) is a newer, off-label antiepileptic/anticonvulsant for NDs that remains underexplored. Recent evidence indicates that prolonged, frequent, and high-dose use of GBP may be associated with an increased risk of various types of dementia and cognitive impairment. GBP has become 1 of the top 20 most prescribed drugs for NDs. GBP modulates voltage-gated calcium channels by binding to the alpha2delta subunit. One possible mechanism is oxidative stress, which can damage neuronal structures, impair synaptic function, and cause mitochondrial dysfunction, all of which are strongly implicated in the pathogenesis of several NDs and contribute to cognitive decline. Another factor is excitotoxicity, where abnormal glutamatergic activity causes excessive calcium influx and neuronal injury, thereby exacerbating mood problems and memory deficits. Long-term use of GBP interferes with SIRT1 (neuroprotective), CaMKII (calcium regulator), and tau phosphorylation regulation, damaging downstream signalling, disrupting central pain pathways in the spinal cord and brain (central sensitisation), damaging neuronal survival pathways, and promoting neurodegeneration. This literature review aims to synthesise current insights on GBP neurotoxic effects, including changes at the gene and protein levels, neuronal structure, function, and network connectivity, as well as strategies for managing GBP-associated NDs. Further research is needed to clarify the exact mechanisms and to develop protective strategies to reduce neurodegenerative risks, optimise seizure control, and evaluate the risks of GBP in clinical settings.